2012
DOI: 10.1002/cyto.a.22102
|View full text |Cite
|
Sign up to set email alerts
|

Polyploidy and chromatin remodeling in hepatocytes from insulin‐dependent diabetic and normoglycemic aged mice

Abstract: Changes in polyploidization, chromatin supraorganization, and chromatin accessibility were investigated in hepatocytes collected from adult, nonobese diabetic (NOD) mice with increasing hyperglycemia and compared with adult normoglycemic controls and 56-week-old normoglycemic BALB/c mice. Our goal was to determine the changes in ploidy degrees and chromatin characteristics in mouse hepatocytes that are associated with insulin-dependent diabetes and to detect similarities in these aspects with those verified wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 44 publications
4
22
0
4
Order By: Relevance
“…A change in chromatin condensation and spatial distribution of high and medium density chromatin components has also been reported with image analysis procedures to be associated with the aging process in the housefly (Panno and Nair 1984). Considering that chromatin remodeling may reflect altered gene modulation (Dejligbjerg et al 2008;Felisbino et al 2011;Ghiraldini et al 2012Ghiraldini et al , 2014, the functional properties of the spermathecal glands of the honeybee queens would certainly be affected by aging. It could be hypothesized that by promoting a protective mechanism against increased oxidative stress in the cells, other cellular functions may be impaired by elevated polyploidization (Anatskaya and Vinogradov 2010), interfering, for instance, with the production of secretions required for the efficiency of sperm-cell preservation in the spermatheca.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…A change in chromatin condensation and spatial distribution of high and medium density chromatin components has also been reported with image analysis procedures to be associated with the aging process in the housefly (Panno and Nair 1984). Considering that chromatin remodeling may reflect altered gene modulation (Dejligbjerg et al 2008;Felisbino et al 2011;Ghiraldini et al 2012Ghiraldini et al , 2014, the functional properties of the spermathecal glands of the honeybee queens would certainly be affected by aging. It could be hypothesized that by promoting a protective mechanism against increased oxidative stress in the cells, other cellular functions may be impaired by elevated polyploidization (Anatskaya and Vinogradov 2010), interfering, for instance, with the production of secretions required for the efficiency of sperm-cell preservation in the spermatheca.…”
Section: Discussionmentioning
confidence: 87%
“…In mouse liver cells, where increased polyploidization is also a well-known characteristic of aging (Gupta 2000;Anatskaya and Vinogradov 2010;Moraes et al 2007;Ghiraldini et al 2012), 122 genes are up-regulated and 77 genes are down-regulated due to aging ). Among the downregulated genes with a ≥2-fold change, several genes were found to be related to signal transduction, transcription, post-translational modifications, and inflammatory responses, and at least four genes were found to be related to chromatin structure and dynamics .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It means that neurons from different regions of brain can have their own genetic programs according to their specific functions or localization, and therefore, could age differently from the others, showing diverse age-associated chromatin configurations. Other studies have found no age-related change in chromatin organization for whole brain, liver, kidney or heart tissue [42,43], or chromatin unpackaging for mouse hepatocytes with aging [44], when subjected to nuclease digestion. It was argued that the non-dividing nature of these cells could be an explanation, since when aged skin fibroblasts were analyzed under the same approach, changes in chromatin organization were found (i.e.…”
Section: Aging Is Associated With Changes In Chromatin Structurementioning
confidence: 92%
“…Hyperglycemia promotes chromatin remodeling and increased polyploidy levels in hepatocytes from non-obese diabetic (NOD) mice; these alterations are similar, but not identical, to the changes observed in hepatocytes from old mice [5]. Recently, it has been observed that the alterations in chromatin organization that occur in hepatocytes from hyperglycemic NOD mice might be orchestrated by the NAD + -dependent histone deacetylases Sirt1 and Sirt6 [6].…”
Section: Introductionmentioning
confidence: 99%